Pengaruh Pengetahuan Ibu Terhadap Permainan Edukasi Berbasis Android Monopoli Gizikia Di Wilayah Puskesmas Talang Ubi Tahun 2025 - Livia Anariyanti (PT. Hasba Edukasi Mandiri, 2026)
The optimization of the golden period of the First 1000 Days of Life is often hindered by the low utilization of the Maternal and Child Health Book due to limited maternal knowledge, while the digital era opens opportunities for health education media innovation through interactive technology platforms. This study aims to analyze the effect of the Android-based educational game application Monopoli Gizikia on increasing knowledge of mothers with children under five regarding maternal and child health. The research employed an experimental pretest-posttest control group design involving 60 respondents of mothers with children under five in the Talang Ubi Public Health Center area, divided into an intervention group (n=30) using the Monopoli Gizikia game and a control group (n=30) with conventional counseling using the MCH Book, with data analysis using Wilcoxon signed-rank test and Mann-Whitney U test. Results showed the intervention group recorded an increase in mean knowledge score of 25.66 points (52.67→78.33), significantly exceeding the control group with an increase of 12.34 points (51.33→63.67), where statistical tests showed a significant difference between the two groups (p=0.002), while the nutritional status of children under five did not correlate significantly with maternal knowledge level. This study concludes that the Android-based educational game application Monopoli Gizikia proved superior in increasing mothers' knowledge compared to conventional counseling methods, offering flexible accessibility and optimal interactive learning to support Maternal and Child Health programs.